Evolvability of Drought Response in Four Native and Non-native Conifers: Opportunities for Forest and Genetic Resource Management in Europe - Schueler, Silvio; George, Jan-Peter; Karanitsch-Ackerl, Sandra; Mayer, Konrad; Klumpp, Raphael Thomas; Grabner, Michael (Frontiers in Plant Science, 2021)
Intra-specific genetic variation in drought response is expected to play an important role in determining the persistence of tree populations in global change as it (1) allows for spontaneous selection and local adaptation of tree populations, (2) supports assisted seed transfer of less drought sensitive provenances, and (3) enables the integration of drought-sensitivity traits into tree breeding. To estimate the potential of such adaptation options requires quantitative genetic knowledge of drought sensitivity across significant parts of species distributions and a comparative assessment of genetic variation within economically and ecologically important tree species. We quantified genetic variation within and among populations of four conifers growing within common garden experiments in the drought-prone eastern Austria. This region experienced three strong drought periods between 1980 and 2010 that resulted in significant reductions of radial growth. Among the four tested species, Douglas-fir revealed the highest resistance during drought and silver fir the best recovery after drought, while European larch and Norway spruce showed the lowest resistance. High genetic variation among populations and phenotypic stability across all three drought events was found for Norway spruce and silver fir, but not for the other species. Heritability and evolvability of drought traits, both approximated via genetic repeatability, revealed strong differences among populations of all four species. Repeatability and evolvability for resistance were highest in Norway spruce and for recovery highest in European larch. Our comparison indicates that mean drought sensitivity of a species is not related to the intra-specific genetic variation in drought response. Thus, also highly drought sensitive species such as Norway spruce and European larch harbor significant genetic variation in drought response within and among populations to justify targeted tree breeding, assisted gene flow and supportive forest management to foster local adaptations to future conditions.